Molecular identification of oomycetes related to horticultural crops in Southern Sumatera and Java, Indonesia - Auliana Afandi; Masanto; Arif Wibowo; Afandi; Supriyono Loekito; Siti Subandiyah; Ayaka Hieno; Kayako Otsubo; Kageyama Koji (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2022)
Indonesia is an agricultural country with more than 30 million farmers nationwide most of it with poor disease management. An identification of a pathogen is the first step to establish efficient management strategies for disease control. In this study, we survey the diversity of oomycetes in horticulture. Samples were collected from 19 sites around Lampung, Sumatera and Java Islands. The oomycetes were isolated from rhizosphere soils sample and from symptomatic plants tissues. One hundred and twelve isolates belonging to two Phytophthora spp., three Pythium spp., and one Phytophythium sp. were identified. Phytophthora nicotianae was a predominant species from pineapple but also found in cabbage, chilli, and chrysanthemum. P. colocasiae were isolated from taro in central java, Phytopythium vexans were isolated from potato in Central Java, while Pythium acanthophoron, Py. myriotylum, Py. splendens, and Py. catenulatum were isolated from soil in pineapple farms.